2006
DOI: 10.1002/ange.200503785
|View full text |Cite
|
Sign up to set email alerts
|

Einelektronenreaktionen von Übergangsmetallkomplexen in der radikalischen Polymerisation

Abstract: Kontrollierte radikalische Polymerisationen sind vor allem dank der Entwicklung effizienter Übergangsmetallkatalysatoren für die radikalische Atomtransferpolymerisation möglich geworden. Eine weitere Methode zur kontrollierten radikalischen Polymerisation ist die metallorganische Radikalpolymerisation, bei der es zur reversiblen Bildung von Metall‐Kohlenstoff‐Bindungen kommt. Übergangsmetallkomplexe können außerdem katalytische Kettentransfers bewirken, einen Prozess, der unter Abstraktion von Wasserstoffatome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Recently, we have shown that the control exerted by [Co-A C H T U N G T R E N N U N G (acac) 2 ] on VAc polymerization occurs by degenerative transfer (DT) when no additional Lewis bases are present, [25] but it switches to reversible deactivation (RD) and more specifically to a process that we have termed "organometallic radical polymerization" (OMRP) [26] in the presence of donor ligands such as pyridine, NEt 3 , or water (see Scheme 1). [25,27] Porphyrin-based cobalt systems have also been shown to function either by OMRP [28][29][30][31] or by degenerative transfer, [32][33][34][35][36] depending on conditions and on the nature of the monomer.…”
Section: ]A C H T U N G T R E N N U N G (Pvac)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have shown that the control exerted by [Co-A C H T U N G T R E N N U N G (acac) 2 ] on VAc polymerization occurs by degenerative transfer (DT) when no additional Lewis bases are present, [25] but it switches to reversible deactivation (RD) and more specifically to a process that we have termed "organometallic radical polymerization" (OMRP) [26] in the presence of donor ligands such as pyridine, NEt 3 , or water (see Scheme 1). [25,27] Porphyrin-based cobalt systems have also been shown to function either by OMRP [28][29][30][31] or by degenerative transfer, [32][33][34][35][36] depending on conditions and on the nature of the monomer.…”
Section: ]A C H T U N G T R E N N U N G (Pvac)mentioning
confidence: 99%
“…Furthermore, the two mechanisms have been shown to coexist for the polymerization of acrylic acid in water. [35] It has been argued that OMRP should be particularly suitable for controlling difficult monomers, [26] because the steric effect of the ligand coordination sphere can be adjusted with a view to fine-tuning the metal-carbon bond strength in a range suitable for control of any desired monomer. The additional advantage of metal complexes is the variety of available transition metals and ligands, which can be tailored to mediate polymerization of the monomer of choice.…”
Section: ]A C H T U N G T R E N N U N G (Pvac)mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] The second process (Scheme 1b) involves a catalytic reversible homolytic cleavage of a carbonhalogen bond through a redox process, which occurs in atom-transfer radical polymerization (ATRP). [15][16][17][18][19] The third one (Scheme 1c) is based on a thermodynamically neutral bimolecular exchange between propagating radicals and a dormant species.…”
Section: H T U N G T R E N N U N G Balta C H T U N G T R E N N U N G mentioning
confidence: 99%
“…[1] We have been interested in the one-electron reactivity of transition-metal complexes and its relevance in CRP. [2] One way in which transition-metal complexes can be used to control radical polymerization is through a reversible deactivation. The growing radical chain is trapped by formation of a metal-carbon bond to yield a metal-capped polymer chain, which is a dormant organometallic species (Figure 1).…”
Section: Dedicated To Jan Reedijk On the Occasion Of His Retirementmentioning
confidence: 99%